Diversity and interdomain networks of bacterial, pico-protist and nano-protist communities in a marine ranching - Zheng, Xinyi; Guo, Xin; Lin, Xiaoqing; Huang, Cheng; Huang, Lingfeng (Frontiers in Microbiology, 2025)
Microbes of diverse sizes and classifications collaborate to mediate a variety of biogeochemical processes. Although seasonal fluctuations in environmental variables generally influence microbial community dynamics, our comprehension of interdomain microbial co-occurrence patterns remains incomplete. Here, we analyzed high-throughput sequencing datasets of bacteria, pico-protists (0.8–2 μm) and nano-protists (2–20 μm), and their seasonal changes in coastal marine ranching ecosystems. Our findings revealed that, in terms of trophic groups, pico-protists predominantly comprised parasites, whereas nano-protists had a higher proportion of mixotrophs. Microbial communities shifted with seasona, mainly in response to temperature, dissolved oxygen, and salinity. Interdomain microbial networks showed the highest robustness and information transfer efficiency in autumn. This pattern was linked not only to environmental conditions but also to how specialized the protist communities became during that time. The seasonal harvesting of seaweed and stages of fish farming may have contributed to these changes. Our findings suggest that both natural seasonal cycles and mariculture activities together shape how microbial species interact, potentially affecting ecosystem stability and function.